Finance e-learning and simulation toward the cloud service environment. (29th March 2011) - Wang, Hsing-Wen
Finance-related courses heavily rely on the statistics and simulation tools to assistant teaching and learning. However, the maintaining costs remaining high, portability still not so well and hard to make license control. Many applications on finance e-learning such as derivatives valuation, portfolios management, scenario simulation, index databases and more can all be accessed from Browser-based browser via mobile platforms or desktop computers. This paper presents a structure of cloud service-based case study for providing a virtual cloud learning environment which combines a wide range of technology and tools to create involve research method for finance e-learning education base on previous studies. The environment is intended for designing and simulation of educational content as well as creating a platform for exploring ideas. The system allows exchange of educational content; integrate different teaching approaches, collaborative learning and easy to learning and teaching under the web service-based cloud environment.